Gender differences in the perception of the indoor environment: Findings from residential buildings in a nordic climate - Theofanis Psomas; Paul O.’ Sullivan; Pavlos Kolias; Adam O.’ Donovan; Pawel Wargocki (Indoor Environments)
Current research suggests gender (“sex assigned at birth”) differences with respect to indoor environmental conditions, indicating females are more critical and demanding towards satisfaction and preferences. The present paper analyzes the results of a subsample of a national survey completed in 375 representative dwellings in Sweden. The survey collected information on twelve comfort factors and satisfaction aspects concerning thermal comfort, indoor air quality, acoustic comfort, satisfaction with daylight, size, standard, layout, appearance, well-being, cost, and neighborhood. Advanced statistical analyses were used to investigate whether the responses of occupants experiencing similar indoor conditions (cohabitation) were different with respect to gender. The analysis did not observe any significant gender differences with respect to the ratings of indoor environments in dwellings. Males reported slightly higher satisfaction, while thermal and acoustic comfort exhibited the highest gender variability. Satisfaction aspects were generally very high, with the costs and acoustic comfort registering the highest levels of dissatisfaction. Additional analyses across various building characteristics and individual attributes (variables levels) confirmed no differences. Several hypotheses were put up to explain these results, including the extreme climatic conditions and the collaborative use of dwellings. The findings suggest that Swedish dwelling designs can provide some best practice guidance for stakeholders and practitioners elsewhere in similar climatic conditions. Future studies should confirm the present observations and the social and cultural aspects of the findings.